SUPPRESSION OF SUBGENOMIC HEPATITIS C VIRUS RNA REPLICON REPLICATION IN Huh-7 CELLS BY THE NS3 PROTEASE INHIBITOR SCH5030334: A STOCHASTIC MATHEMATICAL MODEL - E. L. Mishchenko; N. V. Ivanisenko; I. R. Akberdin; P. S. Demenkov; V. A. Likhoshvai; N. A. Kolchanov; V. A. Ivanisenko (Вавиловский журнал генетики и селекции)
Hepatitis C virus (HCV) causes a severe liver disease frequentlyassociatedwith cirrhosis andhepatocellular carcinoma. No effective anti-HCVtherapyis available so far. Thus, it is pertinent to applymathematical modelingto prediction ofthe efficiencyofnew candidate pharmaceuticals. Astochastic mathematical model for subgenomic HCVreplicon replication in Huh-7 cells with the presence ofthe HCVNS3 protease inhibitor SCH 503034 is proposed. The model describes the experimental kinetic curves ofviral RNAsuppression at various SCH 503034 concentrations. It is applicable to the development ofapproaches to HCVRNAsuppression in Huh-7 cells.